Verbal And Visual Signs in Burger King’s Advertisement - Desilvayanthi, Komang Triska Chandrayuni; Maharani, Sang Ayu Isnu; Saientisna, Made Detriasmita (International Journal of Linguistics and Discourse Analytics, 2026)
In contemporary digital environments, advertising plays a significant role in how people perceive and behave when it comes to choosing products. Brands use strategically selected verbal and visual elements to influence consumers, often implicitly. Although many researchers have examined how advertising can persuade people, there is still a limited integration between semiotic theory and how meaning is actually created in contemporary fast-food advertising practices. This study aims to identify and explain the verbal and visual signs found in selected Burger King advertisements, focusing on how these signs interact to deliver persuasive messages and strengthen brand identity. This research adopts a qualitative method with a semiotic approach. The data were collected using observation and documentation methods from Burger King’s official Instagram posts. Five advertisements were selected based on their extensive use of verbal and visual elements. The data were analyzed using Chandler’s theory of signs (symbolicity, iconicity, and indexicality) and supported by Clair’s theory of color to examine the emotional impact of visual elements. The analysis reveals that verbal signs in the advertisements are predominantly categorized as symbolicity, using familiar cultural expressions and internet language to attract the audience. Visual primarily function as iconicity by realistically depicting food products to evoke appetite, while color choices enhance emotional appeal and visual focus. The study concludes that Burger King successfully integrates verbal and visual signs to create advertisements that are visually appealing, culturally resonant, and emotionally persuasive. These findings highlight the effectiveness of semiotic principles in advertising practice and contribute to a deeper understanding of how fast-food brands construct meaning and identity in the digital space.